Kebersihan Organ Kewanitaan dan Kejadian Keputihan Patologi pada Santriwati di Pondok Pesantren Al Munawwir Yogyakarta - Tri Indah Setiani; Tri Prabowo; Dyah Pradnya Paramita (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Asia in 2013 showed prosentase reproductive health problems of the pathological vaginal discharge were 76%. The incidence of vaginal discharge in the regions Yogyakarta about 68%, in district Bantul about 45% higher than Pondok Pesantren Al Munawwir (59.6%). The purpose of this study was to know relationship between healthy reproductive organ and the incidence of pathology vaginal discgarge on santriwati in Pondok Pesantren Al Munawwir Yogyakarta. The study used survey analytic with cross sectional design. The population of santriwati that experienced vaginal discharge were 164 santriwati. Samples was obtaine by purposive sampling which consisted of 89 respondents, analysis the data was used chi-square. The results of study showed that healthy reproductive organ on santriwati at Pondok Pesantren Al Munawwir Yogyakarta included was 62.9% in less category, incidence of pathology vaginal discharge on santriwati at the cabin al munawwir yogyakarta were 59.6% and the result of χ2 were 8.881 (>8.760). In conclusion, there was a correlation between healthy reproductive organ and the incidence of pathology vaginal discgarge on santriwati in Pondok Pesantren Al Munawwir Yogyakarta.